1967
DOI: 10.1002/jsfa.2740180204
|View full text |Cite
|
Sign up to set email alerts
|

The differential determination of lysine in heated milk. I.—In vitro methods

Abstract: Lysine content and availability were determined in a set of milk samples which had sustained increasing heat treatments. Lysine content was measured after acid hydrolysis of the sample (TLV or x‐value), lysine availability by an enzymic digestion procedure (ALV‐e or y‐value) and by two modifications of the fluorodinitrobenzene method: the direct method (ALV‐f I or z‐value) and Carpenter's corrected straight acid procedure (ALV‐f II or v‐value). The four procedures gave strongly correlated, but numerically quit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Earlier, Ross & Krampitz (1960) and Pion (1961) had both drawn the opposite conclusion, i.e. that FDNB-reactive lysine was not a significantly more sensitive indicator of protein-sugar damage, but Bujard, Handwerck & Mauron (1967) showed that this was due to their use of the Schober & Prinz (1956) procedure for estimating FDNB-reactive lysine content ; this procedure is less specific and more subject to interference from 'caramel' colours in damaged materials.…”
Section: Fdnb-reactive Lysine (Direct Method)mentioning
confidence: 98%
“…Earlier, Ross & Krampitz (1960) and Pion (1961) had both drawn the opposite conclusion, i.e. that FDNB-reactive lysine was not a significantly more sensitive indicator of protein-sugar damage, but Bujard, Handwerck & Mauron (1967) showed that this was due to their use of the Schober & Prinz (1956) procedure for estimating FDNB-reactive lysine content ; this procedure is less specific and more subject to interference from 'caramel' colours in damaged materials.…”
Section: Fdnb-reactive Lysine (Direct Method)mentioning
confidence: 98%
“…Theoretically, the use of enzymes to match those in the human digestive system should provide a good means of hydrolyzing the protein into amino acids, both free and blocked, which could then be analyzed to determine the amount of biologically available lysine. Such enzymic digestions do not reach 100% hydrolysis (use of pronase results in 85% according to Hurrell and Carpenter , 1981b), and hence the figures obtained must be referred to a standard of reference which is taken as 100% and adjusted accordingly (Bujard and others ). Mottu and Mauron () analyzed the availability of lysine in condensed milk and a range of milk powders after enzymatic digestion of the products with pepsin and pancreatin by the method of Mauron and others (), and they compared the lysine figures obtained with those from 3 other methods: acid digestion with lysine analysis, the FDNB method of Carpenter () and an in vivo method based on rat growth (Gupta and others ).…”
Section: Analysis Of Chemically Reactive and Bioavailable Lysinementioning
confidence: 99%
“…At the same period, Carpenter, from Cambridge, developed a chemical test to quantify the availability of lysine in heat‐treated fish proteins, based on the reactivity of the epsilon amino group of lysine with F‐DNB 15. This method was found not to be valid for processed milks (Bujard et al ) 16. An in vivo test was then developed on the rat for the estimation of lysine bioavailability (Mottu and Mauron) 17.…”
Section: The Maillard Reaction In Nutritionmentioning
confidence: 99%
“…15 This method was found not to be valid for processed milks (Bujard et al). 16 An in vivo test was then developed on the rat for the estimation of lysine bioavailability (Mottu and Mauron). 17 The development of chemical tests to measure available lysine (or reactive lysine) in proteins in which the Maillard reaction took place became a challenge involving many international research groups with different approaches: acid hydrolysis, microbiological tests, growth assay in rats, enzymatic digestion, F-DNB, TNBS, guanidination, reduction by NaBH4, dye binding, and others (Hurrell and Carpenter).…”
Section: The Maillard Reaction In Nutritionmentioning
confidence: 99%